Van de Hulst Essay: A review on generalized Lorenz-Mie theories with wow stories and an epistemological discussion. (September 2020) - Gouesbet, Gérard
Highlights: Review on the development of generalized Lorenz-Mie theories. Optical theorem and structured/shaped beams. Speed of light and nature of photons regarding particular effects. Epistemological discussion on the underdetermination thesis of theories by experiments. Abstract: As the 2020 winner of the van de Hulst Award, I have been committed to the writing of a van de Hulst Essay which is presented here. The Award has been essentially motivated by my work on laser light scattering by particles, which spreads over 40 years. During this time, I may have obtained several results of interest, but some of them made me feeling this kind of extraordinary shocks, both emotional and psychological, to which it is only possible to react by a booming "Wow !". Therefore, beside a review on my work on light scattering, the heart of the present paper is devoted to 4 wow stories related to the development of generalized Lorenz-Mie theories. They concern (i) the optical theorem (ii) the speed of laser light, slower than c (iii) the speed of light spots, faster than c and (iv) the "nature" of photons. This last issue required to extend the discussion from pure scientific issues to an epistemological discussion pertaining to the philosophy of sciences.